Transforming Plastic Waste into Ecobrick-Based Creative Economy Products in Kebonsari Village, Surabaya : Transformasi Limbah Plastik Menjadi Produk Ekonomi Kreatif Berbasis Ecobrick di Kelurahan Kebonsari, Surabaya - Muhammad Rafly; Khumairoh Hafiz A’inun Naim; Zahrah Aliyah Rachman; Anatasya Rachma Cahyani; Elsa Aulia Adisti; Tri Lathif Mardi Suryanto (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
The issue of plastic waste in urban areas such as Kebonsari Village requires sustainable solutions that are not only technical but also participatory. This community service activity aims to empower the community through training in the production of ecobricks as a form of transforming plastic waste into creative products with economic value. The method used is participatory-educational, involving residents in every stage of the activity, from education, practical ecobrick making, to the creation of the "Ecorak" book rack. The results of the activity demonstrate an increase in community understanding of environmentally friendly waste management, as well as the creation of ecobrick book racks used in public reading spaces. This activity has a tangible impact in supporting the principles of the circular economy and community empowerment.